Damage evolution in freeze cast metal/ceramic composites exhibiting lamellar microstructures (Fracture and Structural Integrity, 2015)
The damage evolution in a single domain aluminium/alumina freeze-cast composite has been examined using 3D X-ray computed tomography (CT). A single domain was extracted and loaded incrementally at an orientation of 45° to the lamellae, with the damage being assessed after each of eight compressive loading steps. Prior to loading, significant damage was observed at the metal-ceramic interface – this is thought to have formed during machining and can be ascribed to weak interfacial bonding associated with the Cu coating applied to the ceramic preform prior to metal infiltration. Further interfacial damage was seen to initiate after loading to 170MPa and to develop with each subsequent load step. Damage was also observed in the ceramic lamellae, with a series of parallel cracks forming across the alumina, perpendicular to the domain orientation.These sets of parallel, intra-lamellae cracks were closely spaced, but initiated independently, with coalescenceonly occurring at higher loads. Both the interfacial and intra-lamellae cracking initiated after loading to 170MPa,with the intra-lamellae cracks propagating into the metal matrix after loading to 240MPa. The cracks in the ceramic lamellae were found to form and develop independent of the interfacial cracks, with discrete crackpaths and morphologies being observed in each case. Despite this, the underlying driving force was the samefor each damage mode, with crack propagation being driven by an elastic-plastic mismatch between the metalmatrix and ceramic lamellae.
Keywords: Computed tomography